Tungsten carbide-based shape memory biopolymer nanocomposites as a promising new gamma radiation shielding material - Pekdemir, Mustafa Ersin; Yilmaz, Demet; Pekdemir, Sibel Selcuk; Tasgin, Yahya; Ekmen, Busenur (Pergamon-Elsevier Science Ltd, 2025)
In this study, structural, thermal and radiation shielding properties of Polylactic acid (PLA)/polyhydroxyalkanoates (PHAs)/Tungsten Carbide (WC) nanocomposite films were investigated. PHA/PLA/WC composite films were prepared by using different amounts of WC (5%, 10%, 18%, 28%). Characterization of the composite films was carried out by Attenuated Total Reflection Infrared Spectroscopy (ATR-IR), Thermogravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC), X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The linear and mass attenuation coefficients (LAC and MAC), mean free path (MFP), HalfValue Layer (HVL), Tenth Value Layer (TVL), effective atomic numbers (Zeff), and effective electron densities (Nel) of the synthesized composite films were experimentally measured from 53.16 to 383.85 keV. Also, the neutron equivalent dose rates for the prepared film samples were determined. Exposure buildup factor (EBF) and fast neutron removal cross section (Sigma R) were theoretically calculated. The particle shielding characteristics of the composite films were evaluated. The MFP values at 356.01 keV are 8.211 cm, 7.772 cm, 7.360 cm, 6.710 cm and 5.942 cm for PLA/PHA, PLA/PHA/5%WC, PLA/PHA/10%WC, PLA/PHA/18%WC and PLA/PHA/28%WC, respectively. It was observed that an increase in WC content enhances the gamma shielding abilities in PHA/PLA films. The results revealed that PHA/PLA/WC composite materials can be used as protective coating materials.
Keywords: Radiation shielding; Polyhydroxyalkanoates; Polylactic acid; Tungsten carbide; Composite film